Analyzing The Requirements Needed To Align The To-Be Defined OWOW Concept For Boon Edam Service Processes With The SAP FSM Application - Wijaya, Natalia Violi Kristena; Fauzi, Rokhman; Ramadani, Luthfi (eProceedings of Engineering, 2023)
Abstract—Currently, field services are essential in the service sector. Field services set them apart from other services because they offer the opportunity for companies to engage directly with their customers. Technicians as company representatives will have a major impact on customer satisfaction when they perform field services. The better the field service provided, the more satisfied customers are with the company's performance. Therefore, having good field service is the main key to staying afloat in this tight service competition. As the legacy SAP Work Manager at Boon Edam no longer supports them in the service area, the Boon Edam company wants to implement the new SAP Field Service Management (FSM) in hopes of helping them achieve their Global Service Strategy. By analyzing the current situation of how the Boon Edam Service process works and investigating how SAP FSM works, it is hoped that the advice given will help align One Way of Working (OWOW) for Service and SAP FSM. Therefore, it is hoped that the implementation of the SAP FSM Application will run smoothly. The deliverable of the assignment given is an advice in the creation of the to-be defined One Way of Working (OWOW) for Boon Edam Service. The to-be defined OWOW for Service is described in the form of a process flow where this process flow has to include alignment of how Boon Edam Service and SAP FSM work. The main strategy used by the author is to conduct a gap analysis which helps identify what is still missing in the alignment process and how to improve it. At the end of the research, the requirement analysis from the gap analysis resulted that not all alignment processes between the desired requirements and SAP FSM functionality went smoothly. There were also some miss requirements have been found where it seems no functionality within the SAP FSM can carried out in accordance with the desired requirement. Moreover, SAP FSM can cover most of the desired requirements that Boon Edam has. Finally, as part of the recommendation, research on finding out of the box functionality of SAP FSM should be continued. Through that, Boon Edam can maximize the use of SAP FSM and minimize the amount of customization.Keywords—One Way of Working (OWOW), SAP Field Service Management (FSM), gap analysis, alignment process.